The contribution of Escherichia coli from human and animal sources to the integron gene pool in coastal waters - Moura, Alexandra; Araújo, Susana; Alves, Marta S.; Henriques, Isabel; Pereira, Anabela; Correia, António C. M. (Frontiers in Microbiology, 2014)
To understand the contribution of animal- and human-derived fecal pollution sources in shaping integron prevalence and diversity in beach waters, 414 Escherichia coli strains were collected from beach waters (BW, n = 166), seagull feces (SF, n = 179), and wastewaters (WW, n = 69), on the World Biosphere Reserve of the Berlenga Island, Portugal. Statistical differences were found between the prevalence of integrons in BW (21%) and WW (10%), but not between BW and SF (19%). The majority of integrase-positive (intI+)-strains affiliated to commensal phylogroups B1 (37%), A0 (24%), and A1 (20%). Eighteen different gene cassette arrays were detected, most of them coding for resistances to aminoglycosides, trimethoprim, chloramphenicol, and quaternary ammonia compounds. Common arrays were found among strains from different sources. Multi-resistance to three or more different classes of antibiotics was observed in 89, 82, and 57% of intI+-strains from BW, SF and WW, respectively. Plasmids were detected in 79% of strains (60/76) revealing a high diversity of replicons in all sources, mostly belonging to IncF (Frep, FIA, and FIB subgroups), IncI1, IncN, IncY, and IncK incompatibility groups. In 20% (15/76) of strains, integrons were successfully mobilized through conjugation to E. coli CV601. Results obtained support the existence of a diverse integron pool in the E. coli strains from this coastal environment, associated with different resistance traits and plasmid incompatibility groups, mainly shaped by animal fecal pollution inputs. These findings underscore the role of wild life in dissemination of integrons and antibiotic resistance traits in natural environments.